2018
DOI: 10.1159/000468152
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in the Presentation and Management of Cutaneous Melanoma That Required Admission

Abstract: Objective: In this study, we aimed to examine the association of demographic and socioeconomic factors with cutaneous melanoma that required admission. Methods: A cross-sectional study utilizing the Nationwide Inpatient Sample database, 2003–2009, was merged with County Health Rankings Data. Results: A total of 2,765 discharge ­records were included. Men were more likely to have melanoma in the head, neck, and trunk regions (p < 0.001), while extremities melanoma was more common in women (p < 0.001). Males had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…As in previous reports [ 12 , 13 , 14 , 15 ], we identified significant disparities in socioeconomic and health insurance coverage among Black HNSCC patients. Similarly, a SEER database analysis from Taylor et al, showed poorer outcomes in Black patients and demonstrated that socioeconomic status and health insurance were associated with head and neck cancer-specific survival and stage at presentation [ 16 ].…”
Section: Discussionsupporting
confidence: 77%
“…As in previous reports [ 12 , 13 , 14 , 15 ], we identified significant disparities in socioeconomic and health insurance coverage among Black HNSCC patients. Similarly, a SEER database analysis from Taylor et al, showed poorer outcomes in Black patients and demonstrated that socioeconomic status and health insurance were associated with head and neck cancer-specific survival and stage at presentation [ 16 ].…”
Section: Discussionsupporting
confidence: 77%
“…11 In a recently published study on patients with melanoma in the Nationwide Inpatient Sample database, people with a low income and Medicaid coverage were more likely to have worse outcomes. 18 In the field of NETs, black patients with pancreatic NETs had worse survival because of a more advanced stage at presentation and relatively limited access to surgery. 19 However, recent evidence indicates that the racial disparities are going down, and the differences in economic status, insurance coverage, and ease of health care access are becoming more prominent drivers in determining the outcomes of patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Combination therapy with nivolumab and ipilimumab also showed improved overall survival, [12][13][14] leading to approval of the combination in the first-line setting. 11,15 Despite the improvement in outcomes with ICIs for metastatic melanoma, previous studies 16,17 have found that sociodemographic health disparities are associated with limited access to effective therapies for melanoma, including immunotherapy. Underinsurance may be associated with delays in surgery and treatment at low-volume centers.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the improvement in outcomes with ICIs for metastatic melanoma, previous studies have found that sociodemographic health disparities are associated with limited access to effective therapies for melanoma, including immunotherapy. Underinsurance may be associated with delays in surgery and treatment at low-volume centers.…”
Section: Introductionmentioning
confidence: 99%